Tinjauan Matematis Manusia Prima - Hadi, Syaiful (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
There is no unanimous agreement among mathematicians, the so called math. Therefore, to know and understand mathematics can be studied through their characteristics. Based on those characteristics of mathematics, it can be inferred that the analogy of human characteristics in everyday life based on the values of: (1) an agreement, (2) consistency, (3) deduction, and (5) of the universe. Focusing on general characteristics can be mathematically structured review of human excellence based on the concept that human numbers primes that are always close to Allah SWT. and feel that the presence and behavior Allah SWT. willingness.